A study on fetal outcome in patients with oligohydramnios - Chauhan, Rooplekha; Sahni, Sonal; Dubey, Akanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: There is an association between oligohydramnios and intrauterine growth restriction as well as increased perinatal mortality. Amniotic fluid provides a protected environment for the growing fetus, moderating the fetus against mechanical and biological injury. The objective of the present study was to study the fetal outcome in patients with oligohydramnios between 20 to 42 weeks of pregnancy. Methods: Prospective study of 87 pregnancies with oligohydramnios was carried in Department of Obstetrics and Gynaecology, NSCB Medical College, Jabalpur from 1st March 2016 to 31stMarch 2017. All women enrolled for the study were subjected to history taking, clinical examination and amniotic fluid index estimation. Results: Rate of caesarean section was higher in patients with oligohydramnios and higher number of neonates were admitted to the NICU amongst the patients of oligohydramnios. Conclusions: Oligohydramnios has a significant correlation with adverse perinatal outcome.